2013
DOI: 10.1073/pnas.1311310110
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic mitochondrial morphology in monkey prefrontal cortex correlates with working memory and is improved with estrogen treatment

Abstract: Humans and nonhuman primates are vulnerable to age-and menopause-related decline in working memory, a cognitive function reliant on the energy-demanding recurrent excitation of neurons within Brodmann's Area 46 of the dorsolateral prefrontal cortex (dlPFC). Here, we tested the hypothesis that the number and morphology (straight, curved, or donut-shaped) of mitochondria in dlPFC presynaptic boutons are altered with aging and menopause in rhesus monkeys (Macaca mulatta) and that these metrics correlate with dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
174
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(193 citation statements)
references
References 56 publications
11
174
0
Order By: Relevance
“…Both the central and peripheral nervous systems are preferentially affected in patients with systemic mitochondrial diseases (15). Mitochondria are emerging as potent neuromodulators (64) capable of both influencing neuronal development (65) and dynamically regulating synaptic transmission (62,66). In fact, improving mitochondrial antioxidant capacity by the overexpression of catalase specifically in mitochondria increases hippocampal-dependent memory and reduces anxiety (67), further substantiating the notion that changes in mitochondria beyond ATP production can serve a regulatory role on brain function.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Both the central and peripheral nervous systems are preferentially affected in patients with systemic mitochondrial diseases (15). Mitochondria are emerging as potent neuromodulators (64) capable of both influencing neuronal development (65) and dynamically regulating synaptic transmission (62,66). In fact, improving mitochondrial antioxidant capacity by the overexpression of catalase specifically in mitochondria increases hippocampal-dependent memory and reduces anxiety (67), further substantiating the notion that changes in mitochondria beyond ATP production can serve a regulatory role on brain function.…”
Section: Discussionmentioning
confidence: 93%
“…In the brain, mitochondria directly regulate communication between neurons by modifying synaptic structures and neurotransmitter release (62,63). In other cells, mitochondrial dysfunction may repress transmembrane cell-cell communication machinery (18), possibly impairing cellular communication.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the role of mitochondria in regulating synaptic transmission, and less yet about their implications for cognitive function and memory decline in the aging brain (3). The study by Hara et al (4) in PNAS synergizes with recent discoveries, revealing a key role of mitochondria regulating synaptic transmission, brain function, and cognition in aging.…”
mentioning
confidence: 81%
“…Recently it was observed that the amount and morphology of the presynaptic mitochondria in specific brain regions affects memory and synaptic health in non-human primates [25]. The study shows that estrogen treatment, which has been considered to enhance working memory, prevents working memory impairment in aged ovariectomized monkeys.…”
Section: Mitochondrial Function In the Brainmentioning
confidence: 93%